2012
DOI: 10.5430/jbgc.v2n1p116
|View full text |Cite
|
Sign up to set email alerts
|

Early hyperostosis frontalis interna found incidentally by NaF18 PET/CT bone scan

Abstract: The patient is an 80 year old white male who was referred for NaF18 PET/CT bone scan to evaluate for possible prostate cancer metastasis. We found no evidence of prostate cancer metastasis but there was an incidental finding of early hyperostosis frontalis interna in bilateral inner tables of frontal bone on PET/CT scan. The thickness of the inner table of frontle bones was normal on CT scan images; however, increased osteoplastic activity consistent with early active hyperostosis frontalis interna was seen on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…This was the case up to the 50–59 year old age group. Following that, HFI rates appear to remain relatively consistent, as is similarly reported in other research (Fulton, Shand, Ritchie, & McGhee, ; Herschkovitz et al, ; May, Peled, Dar, Cohen, et al, 2011; Nikolić et al, ; Win & Aparici, ). The results of this study, therefore, support the findings of an age‐related increase in HFI reported in the general literature but also confirm a plateau in post‐menopausal age‐related manifestation of HFI in the 50+ year age groups.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This was the case up to the 50–59 year old age group. Following that, HFI rates appear to remain relatively consistent, as is similarly reported in other research (Fulton, Shand, Ritchie, & McGhee, ; Herschkovitz et al, ; May, Peled, Dar, Cohen, et al, 2011; Nikolić et al, ; Win & Aparici, ). The results of this study, therefore, support the findings of an age‐related increase in HFI reported in the general literature but also confirm a plateau in post‐menopausal age‐related manifestation of HFI in the 50+ year age groups.…”
Section: Discussionsupporting
confidence: 83%
“…A review of the clinical literature consistently indicates that severe HFI is found frequently in women who are obese, suffer from type 2 diabetes mellitus, who often display signs of hyperandrogenism (such as hirsutism and acne) and who experience menstrual dysfunction and nulliparity (Barber et al, ; May, Peled, Dar, Cohen, et al, 2011; She & Szakacs, ; Win & Aparici, ). HFI is also found co‐occurring with hyperprolactinemia, hyperphosphatasemia, increased leptin, and progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…Increased tracer uptake in thickened areas of the frontal bone is a frequent finding on bone scintigraphy studies [15] . Increased osteoblastic activity on 18F-NaF positron emission tomography-computed tomography (PET/CT) has been reported without any demonstrable radiographic abnormality which suggests this to be an early marker of HFI [19] . Given tracer uptake appearances can be variable on planar or maximum intensity projection images, this can easily be confounded with bone metastases [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Hyperostosis frontalis interna (HFI) is a benign condition characterized by irregular thickening of the inner table of the frontal bone [1][2][3]. The reported incidence of HFI is between 5 and 12% in the general population [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of HFI is between 5 and 12% in the general population [1,4]. It is more common in postmenopausal females [2,5,6] and has been associated with a variety of clinical conditions including obesity [1,7]. The exact underlying etiology is still unclear but most of the proposed hypotheses suggest the effect of altered sex hormones on the frontal bones [1,3,5,7].…”
Section: Introductionmentioning
confidence: 99%